Implementasi pembagian harta waris di Blok Dungminian, Desa Sumber Kedawung, Kecamatan Leces, Kabupaten Probolinggo: perspektif hukum Islam - Mamlu’atin, Mamlu’atin; Mutamakin, M. (AL-MUQARANAH, 2024)
Islamic law regulates everything very fairly as explained in the Quran, including in regulating the distribution of inheritance that upholds justice. The revelation of inheritance verses gives respect and justice to women, by making women the subject of inheritance makes them happy. However, in reality today, many Muslims divide inheritance assets not in accordance with the verses of the Quran. They consider the application of Surah An-Nisa verse 11 (boys get twice the share of girls) in this day and age is unfair, because now women are more independent, they have the same rights as men in many ways, such as education, work, roles in society and so on, so that the distribution of inheritance is adjusted to their circumstances. That is why researchers feel the need to examine how to solve this problem. The researcher will discuss the implementation of the distribution of inheritance property for the community in Dungminian Block, how also the review of Islamic law on the distribution of inheritance property for the community in Dungminian Block, Sumber Kedawung Village, Leces Subdistrict, Probolinggo Regency. The method used in this research is to use a qualitative approach with data collection techniques in the form of observation, interviews and documentation. The results of the study concluded that the division of inheritance property (tirkah) that occurred in Dungminian Block, Sumber Kedawung Village, Leces Subdistrict, Probolinggo Regency prioritizes family consensus and consensus if no consensus is found, then return to the compilation law and Qur'anic law.